Wounding Induces the Rapid and Transient Activation of a Specific MAP Kinase Pathway. - Bogre, L. (1997)
Mechanical injury in plants induces responses that are involved not only in healing but also in defense against a potential pathogen. To understand the intracellular signaling mechanism of wounding, we have investigated the involvement of protein kinases. Using specific antibodies, we showed that wounding alfalfa leaves specifically induces the transient activation of the p44MMK4 kinase, which belongs to the family of mitogen-activated protein kinases. Whereas activation of the MMK4 pathway is a post-translational process and was not blocked by [alpha]-amanitin and cycloheximide, inactivation depends on de novo transcription and translation of a protein factor(s). After wound-induced activation, the MMK4 pathway was subject to a refractory period of 25 min, during which time restimulation was not possible, indicating that the inactivation mechanism is only transiently active. After activation of the p44MMK4 kinase by wounding, transcript levels of the MMK4 gene increased, suggesting that the MMK4 gene may be a direct target of the MMK4 pathway. In contrast, transcripts of the wound-inducible MsWIP gene, encoding a putative proteinase inhibitor, were detected only several hours after wounding. Abscisic acid, methyl jasmonic acid, and electrical activity are known to mediate wound signaling in plants. However, none of these factors was able to activate the p44MMK4 kinase in the absence of wounding, suggesting that the MMK4 pathway acts independently of these signals.